PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN MENGGUNAKAN CAMTASIA PADA MATERI SISTEM TATA SURYA KELAS VI SD NEGERI 067776 MEDAN JOHOR T.A 2025/2026 - Berliana Afriani Manurung; Lala Jelita Ananda; Eva Betty Simanjuntak; Imelda Free Unita Manurung; Suyit Ratno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop learning video media using Camtasia on the solar system material for sixth grade elementary school using the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 26 students, with data collection techniques in the form of observation, interviews, expert validation questionnaires, teacher and student response questionnaires, and pretest and posttest tests. The results of the study showed that the developed media was categorized as feasible based on the assessment of media design experts (81.66%), material experts (85%), and education practitioners (83.33%). The average pretest score of 42.5 increased to 82.5 in the posttest with an N-Gain value of 0.70 (high category), so that the learning media was declared very effective. Teacher and student responses also showed that the media was easy to use, made learning more interesting, and helped students understand abstract material. Thus, Camtasia-based learning videos can be used as an alternative science learning media for solar system material in elementary schools.